Tomatidine and analog FC04-100 possess bactericidal activities against Listeria, Bacillus and Staphylococcus spp - Isabelle Guay; Simon Boulanger; Charles Isabelle; Eric Brouillette; Félix Chagnon; Kamal Bouarab; Eric Marsault; François Malouin (BMC, 2018)
Abstract Background Tomatidine (TO) is a plant steroidal alkaloid that possesses an antibacterial activity against the small colony variants (SCVs) of Staphylococcus aureus. We report here the spectrum of activity of TO against other species of the Bacillales and the improved antibacterial activity of a chemically-modified TO derivative (FC04-100) against Listeria monocytogenes and antibiotic multi-resistant S. aureus (MRSA), two notoriously difficult-to-kill microorganisms. Methods Bacillus and Listeria SCVs were isolated using a gentamicin selection pressure. Minimal inhibitory concentrations (MICs) of TO and FC04-100 were determined by a broth microdilution technique. The bactericidal activity of TO and FC04-100 used alone or in combination with an aminoglycoside against planktonic bacteria was determined in broth or against bacteria embedded in pre-formed biofilms by using the Calgary Biofilm Device. Killing of intracellular SCVs was determined in a model with polarized pulmonary cells. Results TO showed a bactericidal activity against SCVs of Staphylococcus aureus, Bacillus cereus, B. subtilis and Listeria monocytogenes with MICs of 0.03-0.12 μg/mL. The combination of an aminoglycoside and TO generated an antibacterial synergy against their normal phenotype. In contrast to TO, which has no relevant activity by itself against Bacillales of the normal phenotype (MIC > 64 μg/mL), the TO analog FC04-100 showed a MIC of 8-32 μg/mL. Furthermore, FC04-100 showed a strong bactericidal activity against L. monocytogenes SCVs in kill kinetics experiments, while TO did not. The addition of FC04-100 (4 μg/mL) to a cefalexin:kanamycin (3:2) combination improved the activity of the combination by 32 fold against cefalexin and kanamycin-resistant MRSA strains. In combination with gentamicin, FC04-100 also exhibited a strong bactericidal activity against biofilm-embedded S. aureus. Also, FC04-100 and TO showed comparable intracellular killing of S. aureus SCVs. Conclusions Chemical modifications of TO allowed improvement of its antibacterial activity against prototypical S. aureus and of its bactericidal activity against L. monocytogenes. Antibacterial activities against such prominent pathogens could be useful to prevent Listeria contamination in the food chain or as treatment for MRSA infections.